Passive Leg Raising during Pregnancy - Marques, Nicole Ribeiro; Martinello, Caroline; Kramer, George C.; Costantine, Maged M.; Vadhera, Rakesh B.; Saade, George R.; Hankins, Gary D.; Pacheco, Luis D. (American Journal of Perinatology, 2015)
Objective To determine if passive leg raising (PLR) significantly increases cardiac output in a cohort of healthy pregnant women during the third trimester.Study Design Using a noninvasive monitor, baseline hemodynamic measurements for arterial blood pressure, systolic and diastolic blood pressure, heart rate, cardiac output, cardiac index, stroke volume, and systemic vascular resistances were obtained with patients in the semirecumbent position. Measurements were repeated after a 3-minute PLR maneuver in supine, right lateral decubitus, and left lateral decubitus positions.Results After 10 minutes of bed rest, the cohort's mean baseline heart rate was 80 ± 12 beats/minute. Baseline stroke volume was 98 ± 14 mL, mean cardiac output was 7.8 ± 1.2 L/min, and mean cardiac index was 4.32 ± 0.63 L/min. The baseline systemic vascular resistance value was 893 ± 160 dynes/sec/cm5. Baseline mean arterial blood pressure was 84 ± 11 mm Hg. Following a PLR maneuver in the supine position, heart rate decreased significantly. No difference was noted in other measurements. Findings were similar with PLR in the left lateral decubitus. PLR in the right lateral decubitus resulted in significantly decreased heart rate, cardiac output, and cardiac index.Conclusions PLR did not result in cardiac output recruitment in a cohort of healthy pregnant women during the third trimester.
Keywords: cardiac output; pregnancy; hemodynamics; fluid therapy; passive leg raising; PLR